Coloured brain communication for organization effectiveness - Shamsuddin, Siti Aisyah (Faculty of Medicine, 2022)
The Coloured Brain Communication for Organization Effectiveness Program was held on 6 December to 7 December 2022 and 13 December to 14 December 2022 at Dewan Sri Alam, Hotel UiTM Puncak Alam. This program was organized by the Administration & Human Resources Office in collaboration with the Corporate Communication Unit, Faculty of Medicine UiTM. This program were conducted in two sessions with the first session was for the Faculty Management and Head of the Departments while the second session was conducted for all the staff from departments in the Faculty of Medicine. The main objective of this program is to enhance teams and build cooperation between team members and organizations. The program began with the introductory speech by speaker, Mr. Johan Irwan along with his partner Mr. Arif.